Supercharging engineering biology with automation - Sébastien Lambertucci; Faye Deakin (Engineering Biology)
Abstract Breakthroughs in engineering biology will solve the challenges facing humanity, by harnessing life itself. Standing in the way of these breakthroughs are the technical challenges of collecting the requisite data. Data variability and reproducibility problems, mean the odds are stacked against emerging biotechs. Automation has long been known to solve both problems; Let a robot do the pipetting and get reproducible data with less hands‐on time. Although transitioning to automation has clear benefits, it can introduce additional complexity if done incorrectly. Analytik Jena UK has focused on supporting this transition to automation. We have found the combining of industry expertise with the biology know‐how at the bench is paramount. Great automation should empower the scientist. Scientists should be trained on how to harness their automation. Through industry‐customer relationships, we have successfully automated platforms for building DNA to antibody development. Through this partnership, we can enable a smooth translation of engineering biology to scalable industrial solutions. In this communication we have highlighted some successful examples where translating engineering biology workflows onto automation has proven beneficial, paving the way to industry ready solutions.